Implementing Culturally Responsive Teaching to Improve Critical Thinking and Social Sensitivity in 7th Grade Social Studies - Haryaningtyas Haryaningtyas; Parji Parji; Sudarmiani Sudarmiani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Education is a continuous process that should align with students’ socio-cultural contexts. Culturally Responsive Teaching (CRT) offers an approach that integrates these contexts into the learning process to enhance critical thinking and social sensitivity. This study aims to examine the impact of CRT on the critical thinking skills and social sensitivity of seventh-grade students at SMPN 11 Madiun. This classroom action research was conducted in two cycles, employing Problem-Based Learning (PBL) and Contextual Teaching and Learning (CTL) models. These methods were designed to incorporate students’ cultural backgrounds into Social Science instruction. Students created self-profile videos and explored local folklore as part of the learning activities. In the first cycle, 82% of students demonstrated adequate critical thinking, which increased to 94% in the second cycle. Social sensitivity also improved significantly: initial observations showed that only 43.76% of students met the standard for social sensitivity, while by the end of the second cycle, 100% exhibited empathy and respect for others. The average score of student learning outcomes rose to 90.56, with learning completeness reaching 93.75%. The findings suggest that CRT, when contextualized through culturally relevant materials and learning strategies, can effectively improve students' critical thinking, social awareness, and academic achievement. By creating reflective and culturally meaningful learning experiences, CRT fosters deeper engagement and empathy in the classroom.